Sustainable Food production through organic farming worldwide and locally in Kingdom of Saudi Arabia - Afaf, Almaghamsi (Edelweiss Applied Science and Technology, 2025)
Organic farming is increasingly recognized as a key strategy for sustainable food production, addressing both immediate food demands and long-term agricultural sustainability. This review examines the role of organic agriculture in ensuring food security and environmental sustainability, with a particular focus on its relevance in Saudi Arabia. A systematic review of current research and literature was conducted to evaluate organic farming practices, their impact on soil fertility, and their contributions to sustainable agriculture. Key areas explored include soil health, water conservation, biodiversity enhancement, and the economic viability of organic farming. Findings indicate that organic farming enhances soil fertility, reduces reliance on synthetic inputs, and promotes ecosystem resilience. However, challenges such as yield gaps, economic feasibility, and policy integration require further exploration. The study highlights the need for localized strategies tailored to arid environments to maximize the benefits of organic farming. This review underscores the importance of organic farming in achieving sustainable food systems while addressing global challenges. Practical implications include the adoption of policies that support organic agriculture, investment in research, and the implementation of sustainable farming techniques suited for resource-scarce regions like Saudi Arabia.